Electrical Characteristics of Oxidized/Nitrided Zr Thin Film on Si - Wong, Yew Hoong; Cheong, K.Y. (Electrochemical Society, 2011)
In this work, electrical properties of simultaneously oxidized and nitrided sputtered Zr thin film on n-type Si via N2O gas were systematically investigated and charge conduction mechanisms through the oxide were quantitatively analyzed. Effects of simultaneous oxidation and nitridation duration on the metal-oxide-semiconductor characteristics were reported. It was revealed that 15-min oxidized/nitrided sample showed the highest effective dielectric constant, breakdown field, and reliability. This was attributed to the thinnest interfacial layer, lowest total interface trap, effective oxide charge, and highest barrier height between conduction band edge of the oxide and semiconductor. Depending on the applied electric field and oxidation/nitridation duration, charges were conducted through the oxide via space-charge-limited conduction, Schottky emission, Poole-Frenkel emission, and Fowler-Nordheim tunneling mechanisms.